Emergency obstretic hysterectomy: a retrospective study in a tertiary care center - Shivade, Vaishnavi Sanjay; Vhawal, Vaishali S.; Laddad, Manisha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Obstetric hysterectomy remains a necessity in preventing maternal mortality in catastrophic rupture of the uterus or intractable postpartum hemorrhage when all the conservative management options fail. Uterine atony followed by abnormal placentation remains the primary indication of emergency obstratic hysterectomy worldwide. In majority of cases, anticipation, prompt resuscitation and earlier surgical intervention by skilled operator will reduce patient’s morbidity and mortality. The first successful operation was performed in 1876. The main objective of the study was to study frequency, indications and fetomaternal outcome of emergency obstetric hysterectomy in tertiary care center. Methods: Observational, retrospective and analytical study was done over 2 years from January 2017 to January 2019. A total of 11 cases of emergency obstretic hysterectomy (EOH) were recorded. Results: The overall incidence was 1.47 per 1000 deliveries. Atonic postpartum hemorrhage (54%) was the most common indication followed by placenta previa (18%) and placenta accreta (9%). Second gravida were mostly involved (45%) with previous LSCS (45%) as a common risk factor in commonest age group of 20-25 years (46%) amongst them. The most frequent squeal was disseminated intravascular coagulation (45%). Maternal mortality was nil while neonatal mortality being 9%. The decision of performing total or subtotal hysterectomy along with bilateral internal iliac ligation was influenced by patient’s condition. Conclusions: Emergency obstretic hysterectomy is the most demanding obstretic surgery performed in circumstances of life threatening hemorrhages where conservative surgical modalities fail and interventional radiology is not immediately available. Antenatal anticipation of the risk factors, involvement of experienced obstetrician at the early stage of management and prompt hystrectomy after adequate rescuitation will reduce fetomaternal mortality and morbidity.